Avaliação do perfil nutricional em indivíduos privados de liberdade na penitenciária estadual de Francisco Beltrão: um enfoque na saúde alimentar e bem-estar no contexto carcerário - Bagatini, Raquel Maiéli (2024)
This study aims to investigate dietary and nutritional issues related to the prison lifestyle, with the aim of identifying potential deficiencies, excesses or areas for improvement in dietary practices to contribute to the promotion of health and well-being among individuals in situations of incarceration. The study adopts a cross-sectional observational approach, comprising a sample of 98 male individuals, aged 18 or over, serving closed sentences at the Francisco Beltrão State Penitentiary. The investigation of social, cultural and dietary aspects related to incarceration was conducted using validated questionnaires, together with the collection of blood samples for the analysis of biomarkers associated with the health of inmates. Nutritional deficiencies were identified in the menu, revealing deficiencies in items such as beans and vegetables, while a notable excess in the supply of rice was observed. Despite insufficient daily energy intake among prisoners, it is essential to consider the contribution of food during family visits. Furthermore, the majority of inmates are overweight or obese, influencing energy calculations. Restricting physical activity to a one-hour leisure period in the courtyard, especially on rainy days, contributes to the accumulation of fat and the prevalence of overweight in the prison population. The study population is made up of men aged between 19 and 78 years, predominantly with low education, without a partner, belonging to other ethnicities and with a higher incidence of sexual crimes. Despite the majority reporting good health, there is a high prevalence of depression and changes in Body Mass Index, with the majority of inmates being overweight or obese. Statistical analysis reveals a positive correlation between BMI and age, along with significant associations between BMI and levels of total cholesterol, triglycerides and HDL. Health factors in the prison population can have impacts on the Unified Health System when these individuals are released and seek medical assistance. The study emphasizes the importance of further investigation into prison health, considering it a crucial measure for maintaining the health of inmates, preventing illnesses and contributing to a healthier and more equitable prison environment. These measures, in turn, can ease the burden on prison health systems and contribute to the promotion of general public health.